The Effect of Snoezelen on Psychotropic Drug Use of Nursing Home Residents with Dementia - Boyle, Gail; Bell, Jennifer; Pollock, Clare (The Australian Psychological Society Ltd, 2003)
The purpose of this study was to discover if Snoezelen,an approach that provides sensory stimulation in a relaxing environment,has an effect on the level of psychotropic medication taken by nursing home residents with dementia. There were 3 groups of 22 participants in the study, each matched on Resident Classification Scale (RCS) category( 1 or 2), and age.The 'high' Snoezelen group participated in at least 3 one-to-one Snoezelen sessions per week (over the previous 4eeks), 'low' Snoezelen 1 or 2 per week, and there was a control group ('no' Snoezelen). Information on Snoezelen sessions, diagnoses and medications were obtained fiom nursing home charts. Chi-square analysis found the effect of Snoezelen on neuroleptic(antipsychotic) use significant, as a smaller percentage of the 'high' group took them. The effect on hypnotic/sedative/anxiolytic use was not significant and antidepressant use was the same for the 3 groups.Significant results were found for the effect of Snoezelen on multiple psychotropic use. A significantly larger percentage of the 'high' Sooezelen group took neither neuroleptic medication nor hypnotic/sedative/anxiolytic medication. The effectof Snoezelen on the taking of both neuroleptic and hypnotic/sedative/anxiolytic medications was significant. The percentages of participants in 'high' and 'low' Snoezelen groups taking both psychotropics were significantly smaller.